Superior photothermal black TiO2 with random size distribution as flexible film for efficient solar steam generation. (September 2020) - Zada, Imran; Zhang, Wang; Sun, Peng; Imtiaz, Muhammad; Iqbal, Nousheen; Ghani, Usman; Naz, Raheela; Zhang, Yunxuan; Li, Yao; Gu, Jiajun; Liu, Qinglei; Pantelić, Dejan; et al.
Highlights: Superior photothermal black TiO2 with random size distribution was prepared for efficient steam generation. The vapor generation device was simplified for steam generation process. Black TiO2 with high solar thermal energy conversion surpasses other photothermal materials. The BTiO2 films presented remarkable flexibility and strong mechanical robustness. Abstract: Black photothermal materials with broadband solar absorption have attracted great interest for efficient steam generation. However, the solar steam device composed of thermal insulators and water supply paths makes the device more intricate and problematic to operate. Herein, inspired by random close packing structure of beetle, black TiO2 (BTiO2 ) film with random size distribution is fabricated for simplifying the vapor generation device. The BTiO2 with random size distribution realized a broadband absorption in the full spectrum of solar light (250−2500 nm) due to the plenty of oxygen vacancies/surface disorders/surface defects after the reduction process. When BTiO2 film irradiated under 1 sun illumination, the temperature is quickly changed from 25.4 °C to 90 °C within 120 s which leads to a superior photothermal effect. This high solar thermal energy conversion surpasses other photothermal materials (PMs) reported before. At the same time, when used for steam generation, the solar steam efficiency of 77.14% is achieved under 1 sun solar light irradiation without any thermal insulating management and water supply path. Furthermore, the BTiO2 films presented remarkable flexibility and strong mechanical robustness, which provide a promising approach to design new black materials of different size structures with high mechanical stability/flexibility for developing solar energy-related applications. Graphical abstract: Image, graphical abstract